Inovasi Produk Olahan Hasil Laut dan Jaringan Pasar Dalam Meningkatkan Pendapatan Keluarga Pada Kelompok Nelayan di Desa Labuhan Haji - Wahyu Agus Prianto; Mukmin Suryatni; Salsabila Rizkia Anju; Ni Putu Eka Satvika Devioni; Jumarep; Aranung Hirabella Badjideh; Qothrun Nada; Tia Hariani; Salsabila; Asni Fayanti; Alsyan Izul Muslim (Universitas Mataram, 2026)
Seafood production in Labuhan Haji Village has not been balanced with effective processing and marketing strategies. Most fishermen only sell seafood, especially fish, in fresh form, so the fish quickly spoils. This causes fishermen to often experience losses due to limitations in reaching a wider market. To overcome this problem, an empowerment program was carried out through innovations in processed seafood and marketing strategies consisting of several stages, namely (1) focus group discussions, (2) training on Bage' Fish Processing and Packaging to provide education and training in processing and packaging techniques, and (3) introduction to marketing strategies through comparative studies to one of the successful MSMEs. The results of the activity showed that the training participants, consisting of fishermen's wives, had skills in processing and packaging one of the processed fish products, namely Bage' Fish, using a vacuum sealer. In addition, the introduction to marketing strategies through comparative studies provided participants with insight and skills in establishing partnerships and implementing digital marketing. Training in the processing and packaging of Bage' fish products, as well as an introduction to marketing strategies, has the potential to increase the family income of fishing groups in Labuhan Haji Village, with a profit increase of 30%.Keywords: Fishermen, seafood, processed fish, marketing, Labuhan Haji.